Early Pentecostal Eschatology - Gani Wiyono (Sekolah Tinggi Teologi Satyabhakti, Malang)
Few studies have been devoted to early Pentecostal eschatology.1 One of them, that of by Gerald T. Sheppard merits special attention. Sheppard’s article attempts show that “Pentecostals were not originally dispensationalist-fundamentalist and that the efforts secondarily to embrace such views have raised new problems for the identity of Pentecostals – hermeneutically, sociologically and politically.”2 The procedure taken by Sheppard is to investigate early Pentecostal eschatology as reflected in the writings of some early Pentecostal figures. Unfortunately, he excludes some important earliest Pentecostal figures such as Charles F. Parham, William J. Seymour, and G. F. Taylor. Moreover, some important Pentecostal writers, such as Daniel W. Kerr, that merit special attention due to their distinctive eschatology, have been left out. It is the purpose of this paper to fill “empty space” within Sheppard’s article. It will investigate specifically the eschatological views of Pentecostal writers prior to 1920. The conclusion certainly affirms the Sheppard’ thesis that originally the Pentecostal eschatology was not purely dispensational. Besides, it will be shown that early Pentecostal views on eschatology were not absolutely uniform.